2001
DOI: 10.1152/ajplung.2001.280.3.l527
|View full text |Cite
|
Sign up to set email alerts
|

Intra-amniotic endotoxin: chorioamnionitis precedes lung maturation in preterm lambs

Abstract: The inflammatory and lung maturational effects of intra-amniotic exposure to endotoxin were assessed in fetal lambs. Five hours to 25 days after intra-amniotic injection of endotoxin, preterm lambs were delivered at 119-125 days gestation. Intra-amniotic endotoxin caused an inflammatory cell infiltration in amnion/chorion at 5 h, which persisted for 25 days. At 5-15 h after endotoxin, amnion/chorion cytokine mRNAs increased [12- to 26-fold for interleukin (IL)-1beta, IL-6, and IL-8 mRNA and 3-fold for tumor ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
257
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(287 citation statements)
references
References 51 publications
28
257
1
1
Order By: Relevance
“…This is consistent with our previous findings at 125 d GA regarding treatment after one or two doses of LPS (4,20,21). Our findings show that the increase in neutrophils at 133 d was evidence of a persistent response to the initial inflammatory stimulus.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with our previous findings at 125 d GA regarding treatment after one or two doses of LPS (4,20,21). Our findings show that the increase in neutrophils at 133 d was evidence of a persistent response to the initial inflammatory stimulus.…”
Section: Discussionsupporting
confidence: 93%
“…Chorioamnionitis mediated by intra-amniotic LPS induces unique fetal lung and systemic inflammatory responses (7,8). The normal fetus has intermittent respirations with occasional gasping.…”
Section: Discussionmentioning
confidence: 99%
“…We developed a preterm lamb model of chorioamnionitis in which intra-amniotic LPS directly contacts the fetal lung and causes inflammatory cell influx and expression of proinflammatory cytokines in the fetal lung (7)(8)(9). We also reported that structural changes resembling bronchopulmonary dysplasia (fewer alveoli, vascular injury responses) occur in the preterm fetal lung after exposure to a single injection of intra-amniotic LPS (10,11).…”
Section: Pulmonary and Systemic Endotoxin Tolerance In Pretermmentioning
confidence: 99%
“…51 Proinflammatory cytokine mRNA in the fetal liver was inconsistently and minimally increased; plasma IL-6 and IL-8 levels were minimally increased. 33,49,52 Also, cytokine mRNA levels in the placenta and gut did not increase appreciably. 49 Therefore, a diffuse systemic fetal inflammatory response did not explain the local lung inflammation.…”
Section: How Endotoxin Signals Lung Maturationmentioning
confidence: 91%
“…33,49,50 Diffuse inflammation of the chorioamnion could release effector molecules into the fetal systemic circulation and indirectly induce lung inflammation and maturation. However, intra-amniotic endotoxin had very modest effects on circulating white blood cells and platelets 33,45 and did not adversely affect fetal well-being.…”
Section: How Endotoxin Signals Lung Maturationmentioning
confidence: 99%